Automated house by using raspberry PI - Badri, Shaharudin (2014)
Automated house, house automation or smart house is the same. Basically, this system will allow user or house owner to control or monitor their electrical appliance in their house while they are away. Automated House by Using Raspberry Pi is created by using Raspberry Pi as the central machine that connected to the board controller and this system is fully control via Short Message Service (SMS). No internet connection nor smartphone is needed as long there is a Global System for Mobile (GSM) network in order to access the system. This Automated House by Using Raspberry Pi is easy to use and affordable system that everyone can have it.